The Effect of Sorbitol Concentration on the Characteristics of Starch-Based Bioplastics - Rega Desramadhani; Samuel Budi Wardhana Kusuma (Universitas Negeri Semarang, 2023)
Bioplastics are plastics that can be decomposed naturally by microorganisms into environmentally friendly compounds. One of the natural materials that are widely used to make bioplastics is starch. Potato starch and taro starch have the potential as raw materials for making bioplastics, but it is necessary to increase the brightness of the starch by modifying the starch using NaOCl. Bioplastics made from starch have low mechanical properties, so it is necessary to add a material that can improve mechanical properties, namely a plasticizer. The addition of sorbitol as a plasticizer is expected to improve the mechanical properties of bioplastics. The production of bioplastics begins with the oxidation of potato starch and taro starch, then the plasticizer sorbitol is added with various concentrations of 1.5; 2; and 2.5 (%v). Bioplastics are characterized by testing physical and mechanical properties. The addition of sorbitol concentration affects the physical and mechanical properties produced. The best treatment for the manufacture of bioplastics based on oxidized potato starch and taro starch was obtained at a sorbitol concentration of 1.5% v with a tensile strength of 3.77 MPa and 2.53 MPa, elongation of 19.96% and 8.53%, Modulus Young 18.87% and 29.71%, thickness 0.1669 mm and 0.1517 mm, and water uptake of 74.90% and 66.47%. The results of identification of the functional groups of starch and bioplastics indicated the presence of the same functional groups in the same absorption area. The morphology of bioplastics from oxidized potato starch showed a rough surface, while the surface morphology of bioplastics from oxidized taro starch showed a smooth surface.